2010
DOI: 10.4028/www.scientific.net/amr.152-153.1475
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Antiviral Activity of Calcium Alginate Fibers and Zinc Alginate Fibers

Abstract: The cytotoxicity and anti-influenza virus (IFV) activity of calcium or zinc alginate fibers were investigated to explore the feasibility of them to be used as biomaterials. African Green Monkey kidney cell (Vero) and human cervical cancer cell (Hela) cultured with alginate fibres were used to screen cytotoxic effects. After 48 h, MTT (3-(4,5-dimethyl-2-thiazol)-2,5-diphenyl-2H tetrazolium bromide) assays were performed. Then cytotoxicity was evaluated with six grades according to cell relative growth rate (RGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“… 65 , 66 Calcium and zinc alginate fibers showed antiviral activity on Vero cells with IFV. 62 However, the authors of this study did not specify the IFV type and strain used in the experiments.…”
Section: Alginate-based Materials With Antiviral Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“… 65 , 66 Calcium and zinc alginate fibers showed antiviral activity on Vero cells with IFV. 62 However, the authors of this study did not specify the IFV type and strain used in the experiments.…”
Section: Alginate-based Materials With Antiviral Propertiesmentioning
confidence: 98%
“…As can be seen in Figure 5 , the antiviral properties of alginate against HIV-1 60 , 76 , 77 and HSV-1 51 53 , 61 , 67 69 are the most frequently studied, followed by HCV, 60 , 61 HSV-2, 50 , 68 TMV, 63 , 75 PV-1, 61 , 67 and MNV and HAV. 54 , 59 Alginate-based materials have also been tested against HBV, 60 SINV, 61 RAV, 46 PVX, 48 IFV, 62 VSV, 49 HTLV-1, 60 RV, 47 T4, 72 and HIV-1(VSV). 60 Of these 32 studies, 25 showed viral inhibition, which suggest that alginate-based materials have significant potential as alternative antiviral agents.…”
Section: Alginate-based Materials Against Virusesmentioning
confidence: 99%
“…The antiviral properties of calcium alginate has been hardly explored [11,12]. However, as far as we know, the antiviral activity of calcium alginate with carbon nanofibers and graphene oxide has never been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Alginic acid consists of the linear binary copolymer chains (1,4) linked β-D-mannuronic acid (M), and α-L-guluronic acid (G) residues [2]. Copper alginate fibers, which can be derived from sodium alginate solution by sodium-copper exchange, are new multi-ion antimicrobial fibers that are antistatic and efficient in shielding electromagnetic radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Nontoxic and non-allergenic alginic acid is extracted from bacteria or brown algae including sargassum algae, kelp, and macroalga [1]. Alginic acid consists of the linear binary copolymer chains (1,4) linked β-D-mannuronic acid (M), and α-L-guluronic acid (G) residues [2].…”
Section: Introductionmentioning
confidence: 99%